Relación entre la sintomatología asociada a la depresión, ansiedad y estrés durante la pandemia del COVID-19 en mujeres cabeza de hogar, habitantes del municipio de Uribía del departamento de la Guajira. (2021)
The main objective of this research was to analyze and describe the relationship between symptoms related to anxiety, stress and depression during the coronavirus 19 outbreak in female heads of household residing in Uribía, department of La Guajira. To develop this study, the following dimensions were investigated, clinical approach and integration of mental health, due to the complexity of the disease exposed, it is intended to describe and determine the reasons why cases of stress, anxiety and depression may occur in women head of home, inhabitants of the Uribía municipality of the Guajira department, because the national government ordered mandatory administrative containment as a strategy to contain the virus.